2018
DOI: 10.1002/jcb.27105
|View full text |Cite
|
Sign up to set email alerts
|

FGF9 modulates Schwann cell myelination in developing nerves and induces a pro‐inflammatory environment during injury

Abstract: Myelin sheath is critical for the proper functioning of the peripheral nervous system (PNS), which allows the effective conduction of nerve impulses. Fibroblast growth factor 9 (FGF9) is an autocrine and paracrine protein in the fibroblast growth factor family that regulates cell differentiation and proliferation. Fgf9 Schwann cell (SC) conditional knockout mice were developed to detect the role of FGF9 in the PNS. In our study, the absence of Fgf9 led to delayed myelination in early development. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…FGF9 has been reported to play an important role in the injuryassociated proinflammatory environment, albeit in a neuronal model. 36 In the lung, FGF9 may also be involved in response of reparative cells after injury. 37 The role of EGR2, however, is less clear as it has been shown to be a prosurvival factor involved in inflammation and also a downstream target of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGF9 has been reported to play an important role in the injuryassociated proinflammatory environment, albeit in a neuronal model. 36 In the lung, FGF9 may also be involved in response of reparative cells after injury. 37 The role of EGR2, however, is less clear as it has been shown to be a prosurvival factor involved in inflammation and also a downstream target of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Both Fgf9 and Egr2 were also upregulated upon CEES treatment. FGF9 has been reported to play an important role in the injury‐associated proinflammatory environment, albeit in a neuronal model 36 . In the lung, FGF9 may also be involved in response of reparative cells after injury 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our findings, FGF9 has been characterized as a negative regulator for myelination process in oligodendrocytes as evidenced by multibranched premyelinating oligodendrocytes which interact with nerve fibers but fail to form the myelin sheaths (Lindner et al, 2015). In the PNS, however, FGF9 deficiency led to delayed myelination in early development (Deng et al, 2018). It has been shown that FGF2 inhibits the differentiation from oligodendrocyte progenitor into oligodendrocytes or astrocytes (Azim et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, on the contrary, another report revealed that FGF2 does not block oligodendrocyte progenitor differentiation (Zhou & Armstrong, 2007). From the studies presented above, FGF9 and FGF2 play opposite functions in the process of myelination in different anatomical compartments (Deng et al, 2018; Lindner et al, 2015). Similarly, the NGF‐regulated axonal signals present opposite effects on the myelination process, facilitating SC myelination in the PNS, but reducing oligodendrocyte myelination in the CNS (Chan et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation